Механізація вирощування цукрових буряків з модернізацією копачів комбайна - Циганков, Олег Ігорович; Tsyhankov, Oleh (ЦНТУ, 2024)
Вдосконалено технологічний процес вирощування цукрових буряків шляхом підвищення продуктивності модернізованого комбайна. Проаналізовані конструкції існуючих бурякозбиральних машин та теоретично обґрунтовані раціональні параметри викопувальних робочих органів. Запропоновано вдосконалення конструкції вилок, що дозволить підвищити якість цукрових буряків. В технологічній частині роботи розроблена вдосконалена технологічна карта вирощування цукрових буряків. Розроблені заходи для покращення умов праці і усунення небезпечних та шкідливих виробничих факторів на модернізованому бурякозбиральному комбайні. В економічній частині обґрунтовано економічну доцільність проведених вдосконалень і розробок та підвищення продуктивності вдосконаленого бурякозбирального комбайна. Прогнозований економічний ефект в сумі 9840 грн. The technological process of growing sugar beets has been improved by increasing the productivity of the modernized combine harvester. The designs of existing beet harvesting machines have been analyzed and the rational parameters of the digging working bodies have been theoretically substantiated. An improvement in the design of the forks has been proposed, which will allow to improve the quality of sugar beets. In the technological part of the work, an improved technological map of growing sugar beets has been developed. Measures have been developed to improve working conditions and eliminate dangerous and harmful production factors on a modernized beet harvester. The economic part substantiates the economic feasibility of the improvements and developments carried out and the increase in productivity of the improved beet harvester. The projected economic effect is in the amount of 9840 UAH.
Mechanization of sugar beet cultivation with modernization of harvester diggers
Keywords: цукровий буряк; sugar beet; комбайн; викопувальний пристрій; вилка; технологія; harvester; digging device; fork; technology